A basic study on the application of LRFD in "the technical standard for port and harbour facilities in Japan": a case of gravity type quay wall in a persistent design situation. Issue 3 (3rd July 2019) - Takenobu, Masahiro; Miyata, Masafumi; Otake, Yu; Sato, Takehiko
ABSTRACT: The Partial Factor Method (PFM) based on the Level 1 reliability design method was introduced in 2007 to the Technical Standards for Port and Harbour Facilities (TSPHF-2007) in Japan. After nearly 10 years of practical use of TSPHF-2007, the design standard has been revised based on requests from the practitioners who recommend the transition from the PFM to the Load Resistance Factor Design (LRFD). In this paper, we discuss the setting method of the target failure probability to determine the partial factors based on code calibration. Furthermore, we examine the impacts of implementing the LRFD concept to the TSPHF by taking the sliding and overturning of a gravity type quay wall as an example to represent port and harbour facilities. We found no practical difference in caisson width derived using the LRFD and the PFM, whereas the degree of matching of the target failure probability was somewhat more precise for the PFM. This finding indicates that the LRFD is a more reasonable design method than the PFM in terms of the simplicity of the performance function itself and the ease of engineering interpretation during the design procedure.